THE IMPACT OF GROUP COUNSELING ON PARENTS' STRESS MANAGEMENT DURING EARLY CHILDHOOD DEVELOPMENT: AN EXPERIMENTAL STUDY - Bela Janare Putra; Ega Nur Fadillah (Islamic Counseling and Parenting Journal, 2024)
Development child age early is phase crucial which is often cause pressure psychological impact on parents , which can have an impact negative to pattern care and welfare child . Counseling group offer approach effective to help parents​ manage stress through support social and sharing experience . This study aims to analyze impact counseling group to management parent stress​ during development child age early . This study uses method experimental with pre-test and post-test control group design . The research population consisted of parents who had child age early in city X, with a total sample of as many as 100 people were divided in a way random become group experiments and groups control . Data collected through questionnaire and observation during session counseling group . The results of the study showed that counseling group effective in reducing level parental stress , where there is decline significant on the average score stress group experiment after intervention compared to group control that is not show change significant . This finding supports theory that support social in counseling group capable increase parents' ability to deal with challenge parenting . This study suggests importance integration counseling group as part of a parenting program to reduce stress in development child age early.